Public housing units vs. housing vouchers: accessibility, local public goods, and welfare - Sinan Sarpça; Charles Ka Yui Leung; Kuzey Yilmaz (TÜSİAD-Koç University Economic Research Forum, 2010)
A perennial debate worldwide over housing aid policy focuses on whether the government should provide housing vouchers or subsidized public housing units. To complement the empirically- dominated literature, this paper builds a general equilibrium model that merges urban land use (monocentric city) and Tiebout frameworks. In our model, public housing units or housing vouchers are rationed and some lower-income people have to compete with those with higher incomes in the private rental market. We discuss how location of public housing units is an essential policy variable in addition to the numbers and sizes of units, and argue why housing vouchers may be preferable to public housing.
Keywords: H40; D60; H82; R13; 330; public housing; housing vouchers; housing policy; welfare; residential location choice; local public goods; endogenous sorting; Sozialer Wohnungsbau; Voucher; Soziale Wohnungspolitik; Wohnstandort; Lokales öffentliches Gut; Städtische Bodennutzung; Allgemeines Gleichgewicht; Institutioneller Wettbewerb; Theorie